2009
DOI: 10.4067/s0370-41062009000100006
|View full text |Cite
|
Sign up to set email alerts
|

Resistencia inducible a clindamicina en Staphylococcus aureus meticilino resistente

Abstract: Clindamycin inducible resistance in methicillin-resistant Staphylococcus aureus Background: The increase in methicillin-resistant Staphylococcus aureus (MRSA) infections has limited the use of efective available antibiotics. Clindamycin, an alternative against MRSA, might have inducible resistance that is not detected by common antibiograms. The disk diffusion method (D-test) detects the inducible resistance. Objetive: To establish the frecuency of inducible resistance in MRSA from blood and secretion samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
0
0
6
Order By: Relevance
“…e results of the present study demonstrated that S. aureus isolates from pasteurized cheese in Panamanian markets were resistant to antibiotics from the macrolides class. ese results are in agreement with Montoya's [49], which showed S. aureus resistance to macrolides such as erythromycin and clindamycin from the lincosamide class. Multidrug resistance was observed in forty-two percent (42%) of the S. aureus isolates, including all the antibiotic classes used in the present study (Table 2), as reported by Rivera-Salazar et al [21].…”
Section: Discussionsupporting
confidence: 91%
“…e results of the present study demonstrated that S. aureus isolates from pasteurized cheese in Panamanian markets were resistant to antibiotics from the macrolides class. ese results are in agreement with Montoya's [49], which showed S. aureus resistance to macrolides such as erythromycin and clindamycin from the lincosamide class. Multidrug resistance was observed in forty-two percent (42%) of the S. aureus isolates, including all the antibiotic classes used in the present study (Table 2), as reported by Rivera-Salazar et al [21].…”
Section: Discussionsupporting
confidence: 91%
“…La variable constitutiva (MLSBc) presenta un elevado nivel de resistencia a cualquier antimicrobiano del grupo MLSB; en este estudio se encontró una frecuencia superior a las referenciadas por otros autores y prevalencias muy inferiores a los reportados en otras investigaciones (18)(19)(20)(21)(22)(23)(24). Se encontró una frecuencia del 2 % de resistencia inducible a clindamicina (MLSBi), algunos autores presentan resultados similares a este estudio, mientras que otros trabajos difieren con porcentajes mayores para este fenotipo de resistencia (4,18,19,22,(24)(25)(26)(27).…”
Section: Discussionunclassified
“…Como control se utilizó la cepa de S. aureus ATCC 25923. Se analizaron la presencia de resistencia inducible a clindamicina mediante la prueba del DTest (19), y la susceptibilidad a mupirocina (200 µg) (20,21) y tigeciclina (15 µg), siguiendo las recomendaciones del CLSI (Clinical Laboratory Standards Institute) 2013. Los aislamientos de S. aureus resistentes a meticilina se conservaron en caldo LB (Luria Bertani) con glicerol al 10% a -70 °C.…”
Section: Perfiles De Susceptibilidadunclassified